Psychodiagnostics in the differential diagnosis of depressive disorders of adolescence and young adulthood - Pukhovsky, Богдан; Pilyagina, Галина (Psychosomatic Medicine and General Practice, 2024)
One of the most important problems of clinical psychiatry now is depressive disorders (DD) in adolescents and young adults. They are especially often comorbid with different manifestative features of self-destructive behavior (SDB). Therefore, the intime quality diagnostics and effective treatment of these psychopathological disorders are constantly focused by researchers and require further study. Objective: to study the clinical features of DD and their comorbidity with other psychopathological disorders in adolescence and young adulthood according to sex, and to determine the effectiveness of psychodiagnostic methods in the diagnostics and treatment of these disorders. Materials and Methods. There were examined 64 outpatients (15 – 19 years old) in the study: 14 boys (21.9%, mean age – 17.2 ± 1.5) and 50 girls (78.1%, mean age – 16.6 ± 2.1) with DD, according to the ICD-10. The study included a psychodiagnostic exam with the Beck Depression Inventory (BDI), the Drawing test of E. Warthegg (WZT), and the Purpose in Life Test (PIL). Results. The study identified various types of DD with syndromes comorbidity in the patients. Hystero-depressive syndrome was the most common diagnosis. Girls showed a significant prevalence of these symptoms as well as the depressive-depersonalization/derealization symptom complex, while boys were more likely to have depressive-obsessive and anxiety-depressive syndromes. All examined patients had manifestative features of SDB: suicidal tendencies, suicidal thoughts, and suicidal fantasies. Suicidal thoughts, as well as non-suicidal self-cutting and excoriation in total, were significantly prevalent in girls (p=0.042 and p=0.017). The results of the BDI scale, as part of the psychodiagnostic study, showed that severe depression was significantly more common in girls compared to boys (p=0.007). The study conducted the interpretative analyses of an image content and drawing characteristics according to the WZT. Based on the data formalized by the R. Likert scale, the following types of drawings were identified: primitive, narrative and creative. The 'primitive' drawing was the most frequent type in all patients, with a statistically significant prevalence among boys (p=0.047). Girls showed a higher prevalence of 'creative' drawings compared to boys (p=0.044), with a 4.89 times higher frequency. The results of the PIL test showed that 87.3% of the examined patients had substantially low score of total test index in relation to an average level of normality by sex. And the level of the self-awareness and life meaning averaged 55.1% in boys and only 29.7% in girls, according to the average normative indicators for the test subscales. Conclusions. The study proved the importance of using the BDI, WZT and PIL tests in the differential diagnostics of DD in adolescents and young adults to define the strategy of pharmacotherapy and psychotherapy for these patients.